Prevalence of Varroa destructor in Honeybee (Apis mellifera) Farms and Varroosis Control Practices in Southern Italy - Roberto Bava; Fabio Castagna; Ernesto Palma; Carlotta Ceniti; Maurizio Millea; Carmine Lupia; Domenico Britti; Vincenzo Musella (Microorganisms, 2023)
The majority of honeybee farms in industrialized countries currently base their Varroa destructor control programs on the use of acaricides in conjunction with other management practices. However, the outcomes of these practices are often misunderstood and have only been studied to a limited extent. Better yields are guaranteed by having hives with low infection levels in the spring. Therefore, it is crucial to understand which beekeeping practices can result in increased control effectiveness. This study aimed to analyze the potential effects of environmental factors and beekeeping practices on the dynamics of V. destructor population. Experimental evidence was obtained by interpolating percentage infestation data from diagnoses conducted on several apiaries in the Calabria region (Southern Italy) with data acquired from a questionnaire on pest control strategies. Data on climatic temperature during the different study periods were also taken into account. The study was conducted over two years and involved 84 Apis mellifera farms. For each apiary, the diagnosis of infestation was made on a minimum of 10 hives. In total, 840 samples of adult honeybees were analyzed in the field to determine the level of infestation. In 2020, 54.7% of the inspected apiaries tested positive for V. destructor, and in 2021, 50% tested positive, according to a study of the field test findings (taking into account a threshold of 3% in July). A significant effect of the number of treatments on parasite prevalence was found. The results showed a significant reduction in the infestation rate in apiaries that received more than two treatments each year. Furthermore, it was shown that management practices, such as drone brood removal and frequent queen replacement, have a statistically significant impact on the infestation rate. The analysis of the questionnaires revealed some critical issues. In particular, only 50% of the interviewed beekeepers diagnosed infestation on samples of adult bees, and only 69% practiced drug rotation. In conclusion, it is only possible to maintain the infestation rate at an acceptable threshold by implementing integrated pest management (IPM) programs and using good beekeeping practices (GBPs).